East–West Differences in “Tricky” Tactics: A Comparison of the Tactical Preferences of Chinese and Australian Negotiators - Rivers, Cheryl; Volkema, Roger (2013)
How do Eastern and Western perceptions of “tricky” or ethically ambiguous negotiation tactics differ? We address this question by comparing 161 Chinese and 146 Australian participants’ ratings of the appropriateness of different types of negotiation tactics. We predict that their differing cultural values (e.g., individualism/collectivism, importance of face) as well as their different implicit theories of how negotiation ought to be conducted (i.e., mental models, such as captured in The Secret Art of War: The 36 Stratagems) will be salient in their perceptions of tactics. Examining 24 tactics falling into eight categories, we found that overall the Chinese respondents saw these tactics as more appropriate than did the Australian respondents. There were, however, differences across categories of tactics. Chinese participants rated tactics related to the 36 stratagems as significantly more appropriate than did Australian participants, including diverting attention, misrepresenting information and making false promises. In some cases, the Chinese also saw feigning positive feelings/emotions as more appropriate than did the Australian participants, while an Australian preference for feigning negative feelings/emotions was partially supported. The implications of these findings for practitioners are discussed, along with opportunities for future research.
Keywords: Ethics; Negotiation and bargaining procedures; Australia; China